2018
DOI: 10.1063/1.5023734
|View full text |Cite
|
Sign up to set email alerts
|

Band gap characteristics of radial wave in a two-dimensional cylindrical shell with radial and circumferential periodicities

Abstract: A two-dimensional cylindrical shell (2DCS) structure with radial and circumferential periodicities is proposed in this paper. The band gap characteristics of radial wave propagating radically from the inner circle of the structure are investigated numerically. According to the calculation and discussion of wave transmission behavior, radial wave in the structure is found to show distinct attenuation in certain frequency region, i.e. wave band gap. The internal mechanism of the band gap is then investigated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Among these, many have not even presented anything that properly quantifies or conveys the bandgaps (widths and ranges) of their EBG structures, such as those of [3], [4], [6], [22], [24], [38]- [42]. For the rest (of those without dispersion diagrams) that have at least exhibited some form of EBG characterization, they were through the spectra of transmission/transmittance or mutual coupling [20], [23], [26], [30], [31], [43]- [55], all of which lack the theoretical rigor and scientific depth of the dispersion approach. Such spectra could at best be validations of the latter but should not supersede it as the sufficient portrayal of EBG phenomena in the first place.…”
Section: A) Absence Of Modal Dispersion Diagrams In Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, many have not even presented anything that properly quantifies or conveys the bandgaps (widths and ranges) of their EBG structures, such as those of [3], [4], [6], [22], [24], [38]- [42]. For the rest (of those without dispersion diagrams) that have at least exhibited some form of EBG characterization, they were through the spectra of transmission/transmittance or mutual coupling [20], [23], [26], [30], [31], [43]- [55], all of which lack the theoretical rigor and scientific depth of the dispersion approach. Such spectra could at best be validations of the latter but should not supersede it as the sufficient portrayal of EBG phenomena in the first place.…”
Section: A) Absence Of Modal Dispersion Diagrams In Othersmentioning
confidence: 99%
“…Moreover, the analytical field functions provided here enable the plotting of modal fields (as we have done so as given earlier), something which most other works also fail to match up with. For those few that do present field plots, they were mostly simulated by commercial field solver software rather than via closed-form mathematical expressions [25], [26], [31], [34].…”
Section: ) Analytical Closed-form Mathematical Field Functionsmentioning
confidence: 99%
“…In 2018, Li et al [32] proposed a composite radial plate-type elastic metamaterial composed of periodic double-sided composite branches on a one-dimensional binary radial phononic crystal plate. In 2018, An et al [36] proposed a two-dimensional cylindrical shell structure with radial and circumferential periods. Through the calculation and discussion of wave transmission characteristics, it was found that the radial wave in the design showed apparent attenuation in a particular frequency region, that is, the wave band gap.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the bandgap characteristics of the SMs composed of the periodic arrangement of artificial unit cells. The seismic waves will be attenuated significantly by the SMs in the frequency range of the bandgap [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%